Morbidity and Mortality in Patients with Acute Coronary Syn-drome with and Without Chronic Kidney Disease and Physicans Atitude Regarding Theraphy in the Two Groups - Mădălina Ioana Moisi; Cosmin Mihai Vesa; Larisa Roșan; Otilia Țica; Carmen Dana Zaha; Adriana Ardelean; Babeș Katalin; Mircea Ioachim Popescu (Tehran University of Medical Sciences, 2021)
No Abstract